Optimalisasi Proses Produksi Dan Pemasaran Digital Pada Industri Kerupuk Kulit Sapi Di Kabupaten Banyuasin - Antoni, Darius; Maryani, Maryani; Nurmayanti, Nurmayanti; Suhartini, Suhartini; Harahap, Zakaria; Kurniawan, Kurniawan (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The cowhide cracker industry in Banyuasin Regency represents a micro, small, and medium enterprise (MSME) sector with considerable local economic potential. However, it continues to face a range of challenges, including low production efficiency, limited access to appropriate tools and skilled labour, and suboptimal utilisation of digital media for marketing purposes. This community engagement initiative aims to enhance the production capacity and digital marketing capabilities of local business partners, as part of implementing the Higher Education Tri Dharma, particularly in the area of community service. The approach adopted involved participatory problem identification, training in hygienic and efficient production techniques, assistance in the use of simple production tools, and digital marketing workshops focusing on the effective use of social media and marketplace platforms. The initiative also included efforts to strengthen product branding through the development of attractive packaging and logo designs tailored to consumer preferences. The outcomes of the programme indicate a significant improvement in participants’ understanding of production management and digital marketing strategies. Business partners demonstrated increased independence by actively managing online marketing accounts and adopting improved packaging designs. These results reflect the tangible benefits of the initiative in supporting MSME transformation towards greater competitiveness and resilience in the digital era. Consequently, this activity not only contributed to improving product quality and marketability but also fostered local economic self-reliance through technology-based innovation and the promotion of local creative potential